Agricultural Products Processing and Postharvest Storage - Wu, Bengang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Agricultural products such as fruit, vegetables, and cereal are believed to be some of the most crucial sources of certain phytonutrients necessary for humans, such as vitamins, dietary fibers, and minerals. However, agricultural products are prone to quality deterioration during storage under ambient temperatures. Currently, the annual post-harvest loss rate of agricultural products can reach up to 20-30%. Owing to their perishable nature, the development of processing and preservation technologies for agricultural products is an important research topic closely associated with the national economy and people's livelihoods that has attracted ever-increasing attention. In view of the prominent issues of high energy consumption, high costs, serious pollution, and low-quality properties in agricultural product manufacturing, our journal mainly focuses on research articles on novel techniques and the underlying mechanisms of the processing, preservation, and quality control of agricultural products, so as to promote the upgrading and updating of the agricultural product industry.